Isolation and characterisation of genes involved in carbon and chlorophyll metabolism in Saccharum species hybrids - Fernhout, Jean-Jacque (Stellenbosch : Stellenbosch University, 2015)
Thesis (MSc)--Stellenbosch University, 2015.